49.7k views
3 votes
Evaluate the expression:
2 (m + 1) – n3 when m = -2 and n = 3

User Axi
by
5.1k points

2 Answers

5 votes

Answer:

-29

Explanation:

When number 3 after n is an exponent:

Let m = -2 and n = 3

2 (m + 1) – n³

= 2 (-2 + 1) - 3³

= -4 + 2 - 3³

= -4 + 2 - 27

= -2 - 27

= -29


\tt{ \green{P} \orange{s} \red{y} \blue{x} \pink{c} \purple{h} \green{i} e}

User Bernard
by
5.3k points
5 votes

Answer:

-15

Explanation:

2 * (-4+2) = -6

-6 - 9 = -15

User Sandeep Chatterjee
by
5.4k points